Relationship between androgen deprivation therapy and community‐acquired respiratory infections in patients with prostate cancer. (13th January 2016) - Schmid, Marianne; Hanske, Julian; Ravi, Praful; Krishna, Nandita; Reznor, Gally; Meyer, Christian P; Fisch, Margit; Noldus, Joachim; Nguyen, Paul L; Trinh, Quoc‐Dien
Abstract : Objectives: To investigate the dose‐dependent effect of androgen deprivation therapy on community‐acquired respiratory infections in patients with localized prostate cancer. Methods: We identified 52 905 men diagnosed with localized prostate cancer within the Surveillance, Epidemiology and End Results‐Medicare database between 1991 and 2006. We compared those who did not receive androgen deprivation therapy with those who received androgen deprivation therapy within 2 years of diagnosis, calculated as monthly equivalent doses (<7, 7–11, >11 doses), or orchiectomy. Adjusted Cox hazard models were fitted to predict the risk of community‐acquired respiratory infections (acute sinusitis, acute bronchitis, [severe] pneumonia) in patients treated with medical androgen deprivation therapy versus orchiectomy versus none. Results: Overall, 43.4% received medical androgen deprivation therapy. These patients more likely experienced respiratory events compared with those who did not receive androgen deprivation therapy or who underwent orchiectomy (62.2% vs 54.5% vs 47.8%, P < 0.001). The risk of experiencing any respiratory event increased with the number of doses received. For example, men receiving >11 doses of androgen deprivation therapy were at greatest risk of acute sinusitis, acute bronchitis and pneumonia (HR 1.13, 1.26 and 1.15, respectively, all P < 0.001), except severe pneumonia. Furthermore, we did not detect any relationship between orchiectomy and respiratory events. Study limitations include the utilization of a retrospective population‐based dataset. Conclusions: Increased exposure to medical androgen deprivation therapy for men with localized prostate cancer is associated with a higher risk of community‐acquired respiratory infections. Our results suggest that respiratory complications represent potentially underreported complications of medical androgen deprivation therapy.